2019
DOI: 10.1111/ced.14072
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of kynureninase restrains cutaneous squamous cell carcinoma proliferation and represses the PI3K/AKT pathway

Abstract: Summary Background The protein kynureninase (KYNU) has recently been reported to participate in the pathological processes of various diseases. Aim To explore the expression and the biological function of KYNU in cutaneous squamous cell carcinoma (cSCC). Methods Expression of KYNU in cSCC cell lines and tissues was firstly evaluated based on the Gene Expression Omnibus and the Oncomine databases. Quantitative reverse transcription–PCR was performed to determine the mRNA expression of KYNU in cSCC cell lines. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
2
24
0
1
Order By: Relevance
“…11 KYNU is involved in various inflammatory and cardiovascular diseases, in addition to several types of cancers, acting via different pathways ( Figure 1). [12][13][14][15] Here we discuss the findings, from the literature, supporting the hypothesis that KYNU is a transcriptional target of CD44 as well as known signalling pathways linking the activation of CD44 by HA to the transactivation of KYNU in promoting breast tumour cell invasion.…”
supporting
confidence: 66%
“…11 KYNU is involved in various inflammatory and cardiovascular diseases, in addition to several types of cancers, acting via different pathways ( Figure 1). [12][13][14][15] Here we discuss the findings, from the literature, supporting the hypothesis that KYNU is a transcriptional target of CD44 as well as known signalling pathways linking the activation of CD44 by HA to the transactivation of KYNU in promoting breast tumour cell invasion.…”
supporting
confidence: 66%
“…The results revealed that the 'PI3K-Akt signaling pathway' was enriched (data not shown; Fig. 5A), which has been reported to be associated with the malignant behavior of cSCC cells (26,27). Moreover, the PDPK1 gene was located upstream of the PI3K/AKT signaling pathway (Fig.…”
Section: Mir-451a Overexpression Inhibits Cscc Cell Epithelial-mesencmentioning
confidence: 88%
“…Ci et al found that downregulation of kynureninase inhibited proliferation of cSCC and restrained the PI3K/AKT pathway. 43 Li et al reported that microRNA-374 affected the proliferation, migration, invasion and apoptosis of cSCC cells by targeting Gadd45a through the p53 signaling pathway. 44 However, the mechanism of wogonoside on cSCC has not been clarified.…”
Section: Discussionmentioning
confidence: 99%